2007
DOI: 10.1128/iai.00459-07
|View full text |Cite
|
Sign up to set email alerts
|

Disease Burden Due to Enterotoxigenic Escherichia coli in the First 2 Years of Life in an Urban Community in Bangladesh

Abstract: A cohort of 321 children was followed from birth up to 2 years of age to determine the incidence of enterotoxigenic Escherichia coli (ETEC) in Bangladesh. The average number of diarrheal days and incidence rates were 6.6 and 2.3/child/year, respectively. ETEC was the most common pathogen and was isolated in 19.5% cases, with an incidence of 0.5 episode/child/year. The prevalence of rotavirus diarrhea was lower (10%). ETEC expressing the heat-stable enterotoxin (ST) was predominant. Strains isolated from diarrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
181
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(207 citation statements)
references
References 35 publications
(37 reference statements)
24
181
1
Order By: Relevance
“…Our findings are consistent with other studies that have reported a declining incidence of ETEC diarrhea with age and lower ratios of ETEC infections in symptomatic to asymptomatic children with increasing age (22). Studies have shown that natural protection against ETEC-associated diarrhea emerges in children who are exposed to repeated infections (23)(24)(25)(26)(27); however, natural protection does not prevent ETEC colonization.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are consistent with other studies that have reported a declining incidence of ETEC diarrhea with age and lower ratios of ETEC infections in symptomatic to asymptomatic children with increasing age (22). Studies have shown that natural protection against ETEC-associated diarrhea emerges in children who are exposed to repeated infections (23)(24)(25)(26)(27); however, natural protection does not prevent ETEC colonization.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are of interest, given that current colonization factor-based vaccine approaches do not consider CS7 and CS14 (these factors cross-react immunologically with CS5 and CFA/I, respectively), which may be important causes of pediatric disease (35). Other CFA-toxin phenotype combinations, such as CFA/I-ST and CS5 LT/ST alone, were found in our study to be associated with diarrhea, as well as in a comparable cohort study (27). On the other hand, the combination of LT/ST and CS12 was not found to be associated with diarrhea.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…HBGA phenotype also appears to influence susceptibility to bacterial enteropathogens [86,87], including V. cholerae [88,89]. Nonsecretors are more likely to suffer from severe cholera than secretors [90].…”
Section: Histo Blood Group Antigensmentioning
confidence: 99%
“…Enterotoxigenic Escherichia coli (ETEC) is a causative agent of diarrhea in neonatal and recently weaned pigs as well as humans [10,11]. Treatment of ETEC infection could be easily achieved by the administration of antibiotics, but antibiotic abuse may lead to adverse effects [16] such as antimicrobial resistance, which is a major threat to human health through drug resistance gene transfer.…”
mentioning
confidence: 99%